Fácies e associação de fácies da Formação Piramboia na região de Descalvado (SP) - Côrtes, Ariane Raissa Pinheiro [UNESP]; De Jesus Perinotto, José Alexandre [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2015)
The Piramboia Formation is a lithostratigraphic unit of the Paraná Basin that has been the focus of several studies due to its great importance as an essential component in the Guarani Aquifer System and the Irati-Piramboia petroleum system, consisting of an excellent reservoir. Historically, it was subject to several controversies on issues as age, contact relationships with the upper and lower units as well as its depositional paleoenvironment. However, it is commonly considered as Triassic age and product of wet aeolian systems, with plenty of wet interdunes and subordinate fluvial facies. In this work, the Piramboia Formation was characterized by techniques such as facies analysis, vertical and lateral facies association and depositional architecture based on data from mining fronts at Jundu Mining, Descalvado, northeastern São Paulo. Five facies were described for the Piramboia Formation in the studied region: St, Sh, Sm, Sr and Gt facies, generated by sedimentary processes of bottom load type, mostly under low flow regime. Furthermore, four facies associations were recognized which establish four architectural elements present in the main river channel: complex channel bars, composed by foreset macroforms (FM), sandy bedforms (SB) and gravel bars and bedforms (GB); flood deposits, constituted by laminated sand sheets (LS); deposits of hyperconcentrated flows and aeolian deposits. The results indicate that Piramboia Formation in the study region is the record of the sedimentation of braided rivers, with dunes and interdunes deposits occurring subordinately, characterizing fluvial-aeolian interaction.
Facies and facies association of Piramboia Formation in the region of Descalvado (SP)
Keywords: Architectural elements; Depositional environment; Fluvio-aeolian; Paraná Basin; Piramboia Formation